KESALAHAN POSISI (DISPLACEMENT) DATA HASIL PENGUKURAN ALAT GPS GARMIN 78s TERHADAP DATA PENGUKURAN ALAT TOTAL STATION PADA TITIK - ITIK TOWER SUTT 150 KV AMUNTAI - TAMIANG LAYANG - Gregorius Teofilus Monroe; Suyanto -; Mufidah Asy’ari (Jurnal Sylva Scienteae, 2021)
The government has committed to build a power plant of 35,000 Megawatts (MW) in stages by providing infrastructure in the form of transmission, substations and generating sources. One of the transmissions that can function to distribute from the generator source to the load centers is the 150 kV High Voltage Air Line (SUTT) transmission. The purpose of this study was to analyze the Displacement generated by the Garmin 78s GPS Tool against the Total Station Measurement Data. SUTT 150 kV Amuntai - Tamiang Layang consists of 120 tower points along the transmission line and tower points using Garmin 78s GPS to determine the position of the Total Station data. Position errors in the search for tower points can occur, so the analysis method uses descriptive statistics to find out the real position error on the average of the two coordinate points using Total Station and Garmin 78s GPS. Total Station is a tool used to project tower points. Based on the results of the study, the coordinate position error generated from the 120 tower points is 427.57 meters and the average calibration error is 0.23 (23%) on a weighted average of 3.56 meters.Keywords: displacement; total station; GPS Garmin 78s.